Not for ourselves alone : the story of Elizabeth Cady Stanton and Susan B. Anthony : an illustrated history. - Ward, Geoffrey C.; Saxton, Martha. Gordon, Ann D. (Ann Dexter) DuBois, Ellen Carol, 1947- (New York : A.A. Knopf, 1999)
A companion volume to the PBS film chronicling the 50-year working relationship between suffragists Susan B. Anthony and Elizabeth Cady Stanton.
Includes bibliographical references and index.
PUBLICATION TYPE: Book
Keywords: Feminists -- United States -- Biography; Suffragists -- United States -- Biography; Women's rights -- United States -- History -- 19th century; Women -- Suffrage -- United States -- History -- 19th century; Stanton, Elizabeth Cady, -- 1815-1902.; Anthony, Susan B. -- (Susan Brownell), -- 1820-1906.